Effects of Straw Returning and Chemical Control on Occurrence Quantity of Athetis lepigone Moschler in Summer Maize Fields - Li, Lili; Zhao, Nan; Shi, Jie; Zhang, Ansheng; Men, Xingyuan; Zhou, Xianhong; Zhuang, Qianying; Zhang, Sicong; Wang, Zhenying; Yu, Yi (Plant Diseases and Pests(植物病虫害研究：英文版), 2012)
Athetis lepigone Moschler is a new kind of insect pest occurring in summer corn production areas. By investigation, it was found especially serious in straw returning fields. In this paper, its damage status was investigated in straw returning and chemical controlled fields, respectively. The results showed that the rate of damaged plants was 82% and the maximum pest number per 100 plants was 88 heads in the straw returning fields without chemical control. The application of herbicides and pesticides had no significant effects on occurrence quantity and damage rate, but the pest number per 100 plants decreased a little compared to the fields without chemical control. In the surer er maize fields without straw returning, the application of herbicides and pesticides could significantly decrease the damage of Athetis lepigone, the rate of damaged plants was 20%, and the pest number per 100 plants was 6.